2022
DOI: 10.1007/s11524-022-00626-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Older Black Americans’ Exposure to Structural Racial Discrimination: How Can We Measure the Water In Which We Swim?

Abstract: The USA was built on legalized racism that started with enslavement and continues in the form of structural racial discrimination. This discrimination is difficult to measure because its many manifestations are hard to observe and dynamic. A useful tool would measure across settings, institutions, time periods in a person’s life and the country’s history. The purpose of this study was to design a measure of structural racial discrimination that meets those criteria and can be used in large national datasets. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 22 publications
(40 reference statements)
2
18
0
Order By: Relevance
“…Widespread systemic racism across numerous societal domains (e.g., criminallegal, educational, and political systems; credit, housing, and labor markets; white supremacist ideologies and practices) likely has deleterious effects on Black Veterans' health and resources, as they do in the civilian population. [38][39][40] Our finding that functional disparities decreased when controlling for wealth disparities is in line with prior research indicating that although Black Veterans do experience increases in civilian earnings relative to non-Veterans, these tend to be relatively modest over the long-run and cannot make up for the wealth gaps that exist for Black Americans at birth and persist into old age. 8,41 Prior research has also found that military service may have a "knifing -off" effect of previous experience and disadvantage for Black Veterans.…”
Section: Discussionsupporting
confidence: 88%
“…Widespread systemic racism across numerous societal domains (e.g., criminallegal, educational, and political systems; credit, housing, and labor markets; white supremacist ideologies and practices) likely has deleterious effects on Black Veterans' health and resources, as they do in the civilian population. [38][39][40] Our finding that functional disparities decreased when controlling for wealth disparities is in line with prior research indicating that although Black Veterans do experience increases in civilian earnings relative to non-Veterans, these tend to be relatively modest over the long-run and cannot make up for the wealth gaps that exist for Black Americans at birth and persist into old age. 8,41 Prior research has also found that military service may have a "knifing -off" effect of previous experience and disadvantage for Black Veterans.…”
Section: Discussionsupporting
confidence: 88%
“…A growing body of scholarship operationalizes structural racism as an explicitly multidimensional construct and measure ( 12 , 13 , 68 , 69 , 73 , 74 , 84 , 86 , 91 , 92 , 98 , 106 ). Multidimensional measures can be created with latent-class models incorporating indicators across domains of structural racism as illustrated by Chantarat et al ( 68 ).…”
Section: Resultsmentioning
confidence: 99%
“…Given the complexity of measuring structural racism, some empirical (quantitative) studies may not be appropriate, and qualitative or mixed-method studies should be considered ( 12 , 13 ). For example, qualitative study design (e.g., focus groups) may be ideal for research questions identifying domains of structural racism relevant to their outcome or population, as stakeholders may be more intimately familiar with these interlocking institutions ( 67 , 91 , 104 , 109 ). Examples include Sabo et al's ( 104 ) use of mixed methods to illustrate how anti-immigrant policies may lead to institutional practices that lead to race and ethnicity being conflated with immigration status among residents of Mexican descent, Chambers' ( 67 ) work conducting focus groups with Black women across the reproductive lifespan to generate and validate domains of structural racism, and LaFave et al's ( 91 ) use of interviews and focus groups with older Black adults, discrimination researchers, and stakeholders to design a measure of “structural racial discrimination” for older Black Americans ( 74 , 88 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surveys tend to emphasise experiences of interpersonal discrimination while overlooking systemic and structural discrimination,36 which are equally, if not more, important to address. EDI committees could instead consider critical policy analysis37—evaluating who is disproportionately helped, harmed, or excluded by institutional policies—or measuring systemic indicators of inequity,38 such as the proportion of trainees from certain groups with access to summer research projects. Climate surveys, which assess staff perceptions and perspectives of an organisation, can be used to assess structural discrimination 39…”
Section: Alternative Approachesmentioning
confidence: 99%